A Research of Urban Landscap Transform Detection In Guwahati Region: Impacts of Urbanization on Land Cover and Temperature in Guwahati Metropolitan Area (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Urbanization is without a doubt the real transformationto land cover that significantly impacts biotic differing qualities. Changingurban landscape with high population growth and more interest for land is asignificant issue in Metropolitan Guwahati. The general pattern of urbanizationin Guwahati is unpredictable, various and divided which brings adjustment tocommon land cover inside the city. This complex urbanization process hasadjusted the land surface characteristics inside the city. An examination ofLandsat symbolisms has uncovered resulting diminishing of land cover with adifferent spatial heterogeneity of land surface temperature from 1991 to 2008.To direct the development, the proposed Master Plan for Guwahati 2025 hasappointed some land use zoning. Anyhow the pressure of changing urban landscapehas unmistakably seen over the eco-sensitive and Green belt areas, particularlytowards the outskirts of the city. Because of scarcity of vegetation, a fewhotspots on encompassing hillocks were distinguished, the surface temperatureof which is as high as the downtown. Consequently, here an endeavor has beenmade to correspond variety in temperature with land use sort. The consequenceof the present study is considered to be useful to create countermeasure towarm environmental issue in Guwahati metropolitan area.